Multi-Dimensional Factor Correlation, Multiple Interbank Network Contagion, and Conditional VaR of Banks - Wang, Zhouwei; Zhao, Qicheng; Qiu, Lu (Frontiers in Physics, 2022)
Bank risk is multi-dimensional factor correlation and multi interbank contagion, forming a multi-dimensional multi correlation(MDMC) contagion risk. After superposition, the multiplier effect will magnify the destructive power of a single impact. In this paper, the weighted average method is used to integrate the four interbank infection paths of jump-diffusion, interbank lending, stock price information, and common assets, establish the multi-level interbank infection matrix, apply the quantile estimation of spatial Dubin panel model, estimate the MDMC infectious bank conditional risk value, decompose and identify the systemically important risk factors, systemically important banks, and systemically vulnerable banks. We found the following conclusions. First, the superposition infection effect of MDMC networks is significant. Second, the systemic importance of default risk, interest rate risk, liquidity risk, and GDP growth rate of the banking industry is high, followed by the change of stock market return and investor sentiment. Third, the four major state-owned banks have an MDMC network contagion effect, which has the characteristics of systemic importance and vulnerability.